The Modern Dream of Order - Ehninger, Eva (De Gruyter, 2025)
A fresh exploration of modern photography through the lens of commercial portrait photography - the largest and yet most neglected visual archive of the 19th century. This study explores how commercial portrait photography shaped social relations and provided visual stability in an era of rapid change.